lambda Domain Rate Control Algorithm for High Efficiency Video Coding - Li, Bin; Li, Houqiang; Li, Li; Zhang, Jinlei (IEEE transactions on image processing, 2014)
Rate control is a useful tool for video coding, especially in real-time communication applications. Most of existing rate control algorithms are based on the R - Q model, which characterizes the relationship between bitrate R and quantization Q, under the assumption that Q is the critical factor on rate control. However, with the video coding schemes becoming more and more flexible, it is very difficult to accurately model the R - Q relationship. In fact, we find that there exists a more robust correspondence between R and the Lagrange multiplier λ. Therefore, in this paper, we propose a novel λ-domain rate control algorithm based on the R - λ model, and implement it in the newest video coding standard high efficiency video coding (HEVC). Experimental results show that the proposed λ-domain rate control can achieve the target bitrates more accurately than the original rate control algorithm in the HEVC reference software as well as obtain significant R-D performance gain. Thanks to the high accurate rate control algorithm, hierarchical bit allocation can be enabled in the implemented video coding scheme, which can bring additional R-D performance gain. Experimental results demonstrate that the proposed λ-domain rate control algorithm is effective for HEVC, which outperforms the R - Q model based rate control in HM-8.0 (HEVC reference software) by 0.55 dB on average and up to 1.81 dB for low delay coding structure, and 1.08 dB on average and up to 3.77 dB for random access coding structure. The proposed λ-domain rate control algorithm has already been adopted by Joint Collaborative Team on Video Coding and integrated into the HEVC reference software.